Peran Brand Ambassador, E-Service Quality, dan Persepsi Konsumen dalam Mempengaruhi Keputusan Pembelian di Bukalapak - Novi Wulandari; Eko Agus Alfianto (CV. Satria Jaya, 2025)
This study aims to analyze the influence of Brand Ambassador, E-Service Quality, and Customer Perception on Purchase Decisions on the Bukalapak e-commerce platform, focusing on Bukalapak online consumers. This study found that the majority of respondents were male (67%) aged 21–30 years, educated in high school/vocational school, and worked as employees or private employees. The results of the analysis show that the three independent variables, namely Brand Ambassador, E-Service Quality, and Customer Perception, each have a positive effect on Purchase Decisions. The higher the consumer perception of brand ambassadors and the quality of the electronic services provided, and the more positive the consumer perception of the Bukalapak platform, the greater the likelihood of consumers to make purchases